EFFECT OF ADDITIONAL METHYLENE GROUPS OF TRIPHENYLTIN(IV) COMPLEX DERIVATIVES OF DICARBOXYLIC ACIDS ON CYTOTOXICITY TESTS ON HUMAN PROMYELOCYTIC LEUKEMIC CELLS AND 119Sn NMR RESONANCE - F. W. YIP; Y. FARINA; S. G. TEOH; S. H. INAYAT-HUSSAIN; BOHARI M. YAMIN; I. BABA; A. M. ALI (Universiti Sains Malaysia, 2006)
The complexes of triphenyltin(IV) derivatives of malonic acid (MaH), succinic acid (ScH), glutaric acid (GtH) and adipic acid (DpH) were successfully synthesized and obtained in solid form. The free ligands and complexes were characterized quantitatively using C, H and Sn elemental analysis as well as spectroscopic methods such as infrared (FTIR) and nuclear magnetic resonance (1H, 13C & 119Sn NMR). Results of the analysis on the free ligands and the complexes showed that the coordination took place via one of the oxygen atoms from the carboxylate group. This indicated that the malonate (Ma), succinate (Sc), glutarate (Gt) and adipate (Dp) anions acted as monodentate ligands. 119Sn NMR data showed that additional methylene groups across the ligands in the complexes 1 to 4 caused the 119Sn peaks of the complexes to be shifted upfield. The cytotoxicity of the complexes was tested against promyelocytic leukemic cells, HL-60. The cytotoxic dose (CD50) was determined using microtitration 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Our results showed that the four complexes synthesized gave CD50 values lower than etoposide. Furthermore, the addition of methylene groups to the dicarboxylic ligands causes the CD50 to drop gradually from complexes 1 to 4.